MO133RENAL FUNCTIONAL OUTCOMES AT 5 YEARS FROM RADICAL AND PARTIAL NEPRHECTOMIES IN NORMAL RENAL FUNCTION PATIENTS : AN UNTOLD STORY OF FAILED RENAL HYPERFILTRATIONS. (29th May 2021) - Trevisani, Francesco; Di Marco, Federico; Rosiello, Giuseppe; Fiorio, Francesco; Cinque, Alessandra; Bettiga, Arianna; Capitanio, Umberto; Salonia, Andrea; Montorsi, Francesco
Abstract: Background and Aims: Despite major advance in surgical techniques in the last decade, Chronic Kidney Disease (CKD) is still a major postoperative long-term complication in renal surgery for renal cancer, both in radical than in partial nephrectomy. However, it is still debatable if the renal hyperfiltration mechanism which happens after an acute loss of nephron mass could promote in oncological patients an effective vicariant process over time able to replace a new renal function comparable with the pre-operative one. Aim of our study was to compare the eGFR decay over time from pre-operative time surgery to 5 years follow up in the two major renal surgeries approaches (radical-RN- and partial nephrectomies- PN) in a selected cohort of patients with normal renal function at baseline. Method: We performed a retrospective cohort-study of 271 consecutive patients who underwent radical (RN) or partial nephrectomy (PN) due to the presence of a kidney mass suspected of malignancy from 2000-2020 in a tertiary care urological Institution. Inclusion criteria were: 1) Age > 18 years old 2) eGFR > 80 ml/min/1, 73 using CKD-EPI formula 2012 3) absence of urinary abnormalities . The following data were considered: age, gender, body mass index (BMI), TNM staging, hypertension, diabetes. Glomerular Filtration rate (GFR) was estimated at each time point using creatinine-based estimated glomerular filtration rate (eGFR) formula. We evaluated eGFR variation at the pre-surgical value, hospital dismissal, 6, 12, 24, 36, 48, 60 months. eGFR categories were created according to the KDIGO guidelines for G categories in GFR setting different thresholds. Comparisons between groups were performed using Kruskal-Wallis ranks sum test for numerical variables and Pearson's Chi square test for categorical variables. Logistic regression was used to identify variables ODDS Ratio for AKI onset after surgery. Results: The study cohort was composed by 271 patients with median Age 56 (IQR: 48, 64), M/F ratio 2.3, median BMI 25.7 (IQR: 23.3, 28.3), median eGFR 94.3 (IQR: 89.1, 101.3) mL/min/1.73m^2. According to CKD G class, 70% were I and 30% were II. The cohort was divided in two groups according type of surgery: 44% as RN and 56% as PN. Differences between the two groups were detected for Gender (Radical M/F ratio: 3.2; Partial M/F ratio: 1.8; p=0.4), basal eGFR (Radical Median:92.3 (88.0, 99.8) mL/min/1.73m2; Partial Median:95.4 (90.1, 102.0) mL/min/1.73m2; p=0.01) and CKD G class (Radical I:64%, II:36%; Partial I:76%, II:24%; p=0.03). Two-way Anova for time variation of eGFR according other parameters, enlightened a significative difference for the type of surgery (p<0.001): in particular, the analysis showed the presence of a variation over time of the eGFR (p<0.001) that depends also on the surgery type (p<0.001). Post-hoc analysis showed the impact of the differences in term of eGFR decay at different time points: at 6 months the radical nephrectomy groups had a mean decay higher (p<0.001) by 19 mL/min/1.73m2.(13.2, 24.9), at 12 months (p<0.001) by 19.6 mL/min/1.73m2.(14.9, 24.3), at 24 months (p<0.001) by 18 mL/min/1.73m2.(11.9, 25.2), at 36 months (p<0.001) by 15.4 (9.4, 21.4), at 48 months (p<0.001) by 16, 4 (10.4, 22.3) and at 60 months (p<0.001) by 15 (11.2, 18.7) mL/min/1.73m2 (Figure 1 ) Conclusion: Our study highlights that both RN than PN harbor a non negligible risk of post-operative CKD events even in normal renal function patients without renal abnormalities at 5 years from the operations. However, RN patients display a different behavior in term of renal compensation in respect of PN. In fact, RN pts tend to replace the acute loss of function derived from the absence of the contralateral kidney with an increase of eGFR, whereas PN pts tend to remain stable over time without any effort of hyperfiltration. A prospective comparison multicentric study with kidney living donor is on going.